Python Programming - Limited, Learnkart (Packt Publishing, 2020)
Gain hands-on experience with Python and Django and learn essential Python concepts About This Video Learn the basics of Python Understand input-output functions Explore software installation and environment set-up In Detail Python is the future of AI and machine learning and one of the most popular programming languages in the world. This course will help you understand Python's design, memory models, object-arranged highlights, and more. You'll start with the basics of Python before moving on to explore data operations. The course will guide you through everything, from data conversion to list methods. As you progress, you'll also get to grips with error handling and file operations. Toward the concluding sections, you'll focus on web scraping using Beautiful Soup, before finally going on to understand Django. By the end of this course, you'll have skills you need to confidently create and send robust Python applications using off-the-rack libraries.